Reading the Transformation of Ottoman Sultan Complexes in Bursa in Urban and Architectural Scale Since 19th Century - Durak, Selen; Vural Arslan, Tulin; Fetullahoglu, İpek; Ceren Saglık, H. (European Journal of Sustainable Development, 2017)
The first Sultan Complexes (kulliyes) of the Ottoman Empire, built in Bursa during the 14th and 15th centuries, played an important role in the formation of residential buildings around and in determining the main transportation axes in the development of the city. These five complexes, including social and religious buildings, left significant traces in cityscape until the 20th century, in addition to their spiritual values in urban history and became an integral part of urban identity. From the 20th century onwards, the developing dynamics of cities threatened the sustainability of monumental buildings and endangered their original identity. Bursa was included in UNESCO World Heritage Site list in 2014 with these complexes that preserved their authenticity and integrity in large despite these changes. However, high-rise buildings in the city began to dominate cityscape and the visibility of the complexes in the city skyline gradually disappeared. In this study, transformation of Sultan Complexes of Early Ottoman Period in Bursa has been analysed in terms of urban and architectural scales from the 19th century onwards. By comparing 1862 Suphi Bey map – the first city map including the most comprehensive information about the urban fabric of Bursaand the actual city map, changes in urban fabric around the complexes have been identified. In addition, comparison of the 19th century city photographs and engravings with actual photographs helped to reveal the changes in city skyline and the transformations in architectural scale. Keywords: Urban identity, Ottoman Sultan Complex (kulliye), Bursa